2013
DOI: 10.1016/j.jpsychores.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Gender and cognitive–emotional factors as predictors of pre-sleep arousal and trait hyperarousal in insomnia

Abstract: Objective Elevated pre-sleep arousal has been consistently associated with insomnia, yet the cognitive-emotional mechanisms involved in sleep-related arousal remain unclear. The purpose of this study was to identify predictors of pre-sleep arousal and trait hyperarousal from a set of variables that included self-reported affect, sleep-related cognitions, locus of control, and gender. Methods Cross-sectional data were analyzed for 128 participants (89 female) who met criteria for psychophysiological insomnia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 52 publications
3
25
0
3
Order By: Relevance
“…Examples are posttraumatic stress disorder (Edmondson and Cohen, 2013; Perez et al, 2012), attention deficit hyperactivity disorder (Antshel et al, 2013; Hanson et al, 2012), general anxiety disorder (Brunet et al, 2013; Hoge et al, 2013), insomnia (Hantsoo et al, 2013; Killgore et al, 2013; Vincent and Walsh, 2013; Wallhausser-Franke et al, 2013), and Fragile X syndrome (Berry-Kravis et al, 2012; Heilman et al, 2011). Autonomic dysregulation is an aspect of some of these disorders, but sighs have not been specifically characterized in these disorders, (Beauchaine et al, 2007; Heilman et al, 2011; Kalk et al, 2011; Musser et al, 2013).…”
Section: When Sighs Enhance Breathing Variability and Induce Hyperamentioning
confidence: 99%
“…Examples are posttraumatic stress disorder (Edmondson and Cohen, 2013; Perez et al, 2012), attention deficit hyperactivity disorder (Antshel et al, 2013; Hanson et al, 2012), general anxiety disorder (Brunet et al, 2013; Hoge et al, 2013), insomnia (Hantsoo et al, 2013; Killgore et al, 2013; Vincent and Walsh, 2013; Wallhausser-Franke et al, 2013), and Fragile X syndrome (Berry-Kravis et al, 2012; Heilman et al, 2011). Autonomic dysregulation is an aspect of some of these disorders, but sighs have not been specifically characterized in these disorders, (Beauchaine et al, 2007; Heilman et al, 2011; Kalk et al, 2011; Musser et al, 2013).…”
Section: When Sighs Enhance Breathing Variability and Induce Hyperamentioning
confidence: 99%
“…The most prominent model in dream research, the continuity hypothesis (Hall & Nordby, 1972), states that the dream is largely a reflection of the individuals' waking experiences (for a review, see Domhoff, 2003;2010). As such, this model could suggest that the negative pre-sleep cognitive arousal (for a review, see Hantsoo et al, 2013) experienced by patients with PI could translate into their dream activity, resulting in more negatively toned dreams. Moreover, knowing that patients suffering from PI generally display more neuroticism, and dysfunctional beliefs about sleep and that insomnia is characterized by negative daily consequences and concerns such as physical/psychological health problems, fatigue, mood disturbances and cognitive alterations (Beaulieu-Bonneau, LeBlanc, Vérette, Dauvilliers, & Morin, 2007;Morin et al, 2011;Van de Laar et al, 2010), it would be reasonable to assume that the dreams of PIs would be negatively affected and they would report more nightmares than normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-sleep arousal was common among individuals with sleep disorders, and it was an important etiological factor of insomnia disorders [21]. It has been reported that insomnia patients have somatic, cognitive, and cortical arousal [22][23][24][25]. Sleep plays a very important role in mediating multiple domains of affective functioning including emotion, emotion memory, and emotion regulation.…”
Section: Discussionmentioning
confidence: 99%